IDENTIFICATION OF BIOACTIVE COMPOUNDS IN FLOWER OF TABERNAEMONTANA DIVARICATA (L.) USING GAS CHROMATOGRAPHY–MASS SPECTROMETRY ANALYSIS - KALAIMAGAL C (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Herbs are a key resource with therapeutic properties. Nowadays, there is a focus on the identification of bioactive compounds with the ability to act against various disorders. Methods: In the present study, gas chromatography–mass spectrometry analysis was conducted to determine the occurrence of different phytochemical compounds in ethanolic flower extract of Tabernaemontana divaricata (L.). Results: The ethanol extract of flower revealed the presence of several bioactive compounds such as n-hexadecanoic acid, squalene, Vitamin D3, Vitamin A aldehyde, desulfosinigrin, and Urs-12-en-24-oic acid, 3-oxo-, methyl ester, (+)-. Conclusion: The perceived compounds from ethanolic extract of flower have diverse beneficial properties such as antimicrobial, antioxidant, cancer anticipatory effect, pesticide, and antiarthritic.